The prophetic quest the stained glass windows of Jacob Landau : Reform Congregation Keneseth Israel, Elkins Park, Pennsylvania - Herrstrom, David S. 1946-; Scrimgeour, Andrew D. 1945- (The Pennsylvania State University Press, 2021)
"Explores ten monumental stained-glass windows, designed by the artist Jacob Landau, for the Keneseth Israel synagogue in Elkins Park, Pennsylvania"--
Keywords: Landau, Jacob -- 1917-2001; Landau, Jacob / 1917-2001 / Criticism and interpretation; Reform Congregation Keneseth Israel (Elkins Park, Pa.); Stained glass windows / Pennsylvania / Elkins Park / History / 20th century; Jewish art and symbolism / Pennsylvania / Elkins Park / 20th century; Prophets in art; Landau, Jacob / 1917-2001; Jewish art and symbolism; Stained glass windows; Pennsylvania / Elkins Park; 1900-1999; Criticism, interpretation, etc; History